Narrating China's Governance Stories in Xi Jinping's Speeches - People's Daily, Department of Commentary; People's Daily, Department of Commentary (Springer, 2020)
Preface -- Introduction: .-Part 1 About the Interior -- On Incorrupt Government: "When the officials become corruptible and unfair, the regime is going into decline" -- On Characters and Morals: "To enter politics, a person should cultivate his moral character and enrich himself with virtues first" -- On Self-improvement: "If you want to enhance your ability, you must study; if you want to make the blade sharp, you must sharpen it"- On Governance: "Empty talk endangers the nation, practical work brings prosperity" -- Part 2 About Diplomacy -- On People-to-people Friendship: "The key to sound relations between states lies in amity between the people" -- On Intercourse Between Nations: "Of the things brought about by the rites, harmony is the most valuable" -- On Cultural Exchange: "It is the very nature of things to be unequal in quality" -- On Historical Affinity: "Distance cannot separate true friends who feel so close even when they are thousands of miles apart" -- On Xi Jinping's Personal Experience: Never forget why you started
Keywords: History of China; China—History; Ethnology—Asia; Political science; Culture.